수격펌프의 효율성 및 현장 적용성 평가 - 이수형(Soo-Hyoung Lee); 윤희성(Heesung Yoon); 김동훈(Dong-Hun Kim); 신에스더(Esther Shin); 김용철(YongCheol Kim); 고경석(Kyung-Seok Ko); 하규철(Kyoochul Ha) (자원환경지질, 2016)
This study was conducted to evaluate the applicability and efficiency of water supply using hydraulic ram pump. Study area is the Imgok-ri, Hwanam-myeon, Sanju-si, Kyeongsangbuk-do. There is an abandoned coal mine, where groundwater is discharged from its entrance with a flow rate of approximately $260m^3/day$. Hydraulic ram pump uses the waterhammer phenomenon and utilizes the power of falling water for pumping part of that water to a higher elevation than the water sources without electric power. To determine the efficiency of hydraulic ram pump, the flow rate was measured at three points according to the altitude difference (${Δ}h=19m$ (point 1), 30 m (point 2), 40 m (point 3)). Flow rate measured at 1, 2, and 3 were about $8.6{\sim}10.8m^3/day$, $3.98{\sim}4.39m^3/day$, and $2.35{\sim}2.59m^3/day$, respectively. The current results suggested that, hydraulic ram pump could be applicable for the water supply system in mountain areas without external power supply. 본 연구는 수격펌프를 이용하여 용수 공급의 가능성과 효율성을 평가하기 위하여 수행되었다. 연구지역은 경상북도 상주시 화남면 임곡리로 과거 석탄개발에 사용된 갱도로부터 지속적으로 지하수 유출이 발생하고 있다. 유출되는 지하수는 일평균 약 $260m^3/day$의 수량을 가지는 것으로 파악되었다. 수격펌프는 수격현상을 이용하여 전력없이 공급원으로부터 고도차(압력)에 의해 물의 일부를 높은 곳으로 이송시키는 펌프이다. 수격펌프의 효율성을 파악하기 위해 수격펌프와의 고도차에 따라 3지점(${Δ}h=19m$ (1지점), 30 m (2지점), 40 m (3지점))에서 유량을 측정하였다. 1지점에서는 약 $8.6{\sim}10.8m^3/day$, 2지점은 약 $3.98{\sim}4.39m^3/day$ 그리고 3지점에서는 약 $2.35{\sim}2.59m^3/day$의 물을 운반할 수 있는 것으로 파악되었다. 이번 연구를 통해 수격펌프가 산간지역 등에서 전력없이 물공급 시스템에 활용할 수 있을 것으로 파악되었다.